1999
DOI: 10.1038/emm.1999.17
|View full text |Cite
|
Sign up to set email alerts
|

Development of two novel nontoxic mutants of Escherichia coli heat-labile enterotoxin

Abstract: Abbreviations: ETEC, enterotoxigenic Escherichia coli; LT, Escherichia c o l i h e a t -l a b i l e enterotoxin; CT, cholera toxin; GM 1, monosialoganglioside; ELISA, enzyme-linked immunosorbent assay AbstractEscherichia coli heat-labile enterotoxin (LT) is composed of catalytic A and non-catalytic homo-pentameric B subunits and causes diarrheal disease in human and animals. In order to produce a nontoxic LT for vaccine and adjuvant development, two novel derivatives of LT were constructed by a site-directed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…In contrast, the B subunit, the part of the molecule that binds to the cell surface via G M1 (or other gangliosides) and facilitates entry of the holotoxin into the cell, has an as yet an uncertain adjuvant effect. This arises from the fact that the adjuvant activity of the A subunit is largely retained in modified toxins in which the ribosyltransferase activity has been greatly attenuated by site-specific mutagenesis (33,34). Thus, many earlier studies conducted with purified B subunit are suspect since purified B subunit may contain sufficient amounts of A subunit to reflect A subunit effects rather than B subunit effects (8,9).…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, the B subunit, the part of the molecule that binds to the cell surface via G M1 (or other gangliosides) and facilitates entry of the holotoxin into the cell, has an as yet an uncertain adjuvant effect. This arises from the fact that the adjuvant activity of the A subunit is largely retained in modified toxins in which the ribosyltransferase activity has been greatly attenuated by site-specific mutagenesis (33,34). Thus, many earlier studies conducted with purified B subunit are suspect since purified B subunit may contain sufficient amounts of A subunit to reflect A subunit effects rather than B subunit effects (8,9).…”
Section: Discussionmentioning
confidence: 97%
“…These mutant LTs were shown to be immunogenic in a previous study and induce high titers of LT-specific antibodies following IG and IN immunization (Park et al, 1999). In the present study, the mutant LTs showed no ADP-ribosyltransferase activity, but retained adjuvant activity.…”
Section: Discussionmentioning
confidence: 53%
“…We previously showed that both mutant LTs were immunogenic following either IG or IN administration, and that antibody titers induced by IN immunization were slightly higher than those induced by IG immunization (Park et al, 1999). In the present study, the abilities of mutant LTs to act as mucosal adjuvants were assessed by IG immunization in mice.…”
Section: Mucosal Adjuvanticity Of Mutant Lts In Ig Immunizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the infected intestinal cell secretes chloride and water, leading to typical symptoms of diarrhea. In vitro assays confirmed the activation of the adenylate cyclase and showed that Chinese hamster ovary (CHO) target cells were elongated after intoxication with Ctx and LT, suggesting morphological changes attributed to the increased cAMP level [10,11].…”
Section: Introductionmentioning
confidence: 89%